Extreme hyponatremia due to the syndrome of inappropriate antidiuretic hormone secretion (SIADH) in a patient with small cell lung cancer – a case report and literature review - Ząbek, Magdalena; Szpytma, Teresa; Gliński, Bogdan (Contemporary Oncology/Współczesna Onkologia, 2005)
Introduction: A case of symptomatic SIADH syndrome with an extremely low sodium level occurring at the beginning of the treatment course in a patient with small cell lung cancer is described. Case report: A 64-year-old man with histopathologically confirmed small cell lung cancer was admitted to the Radiation Oncology Department in good general condition. The staging was established as limited disease, biochemical parametres were normal. Systemic treatment basing on cisplatin and etoposide was started. On the fourth day of chemotherapy the patient demonstrated weakness, anorexia, nausea, vomiting, then three episodes of seizure. He was in altered mental state, confused. Basing on biochemical parameters and after excluding other causes, the SIADH syndrome was diagnosed. Intravenous infusion of hypertonic saline and symptomatic treatment resulted in both clinical state and biochemical parameters improvement. Discussion: The most frequent malignancy connected with ectopic ADH secrection is small cell lung cancer. The occurrence of SIADH in SCLC patients is 8-10%. The peculiar intensity of hyponatremia and the dynamism of its appearance indicate the sudden nature of the active substance release. Its possible mechanisms are: ADH release from cancer cells due to their lysis after initial treatment and ortotropic secrection of ADH as a result of stimulation by cytostatics, particularly cisplatin. The first signs of the SIADH syndrome may be taken as a part of the main disease clinical picture, reaction to treatment, malignancy progression to the central nervous system. The SIADH syndrome occurring at the beginning of treatment course may be a sign of either the effectiveness of treatment (ADH release during the initial tumour cell lysis) or the therapeutic failure (ADH secretion from alive cancer cells, disease progression). The described case of extreme hyponatremia (as life-threatening state) shows the need for careful monitoring of patients at the beginning of antineoplastic treatment course.